1993
DOI: 10.1128/iai.61.2.588-595.1993
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of fibroblast-activating factor isolated from Porphyromonas gingivalis W50

Abstract: A 24-kDa polypeptide which activated the incorporation of [3Hlthymidine into human fibroblasts was isolated from the outer membrane vesicles of Porphyromonas gingivalis W50. This polypeptide, named fibroblast activating factor (FAF), was isolated by 3-[(3-cholamidopropyl)-dimethyl-ammonioJ-1-propanesulfonate (CHAPS) detergent extraction and purified by DEAE ion-exchange chromatography and preparative isoelectric focusing. Purified FAF (100 ng of protein per ml) caused a 400%o increase in [3H]thymidine incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…These improvements made it possible to isolate substantial amounts (>30 mg per liter of the culture) of highly purified protein and facilitated a more detailed protein analysis. In this study, we characterized two HmuY variants: a mature HmuY protein (mHmuY) lacking 21 N-terminal amino acids and a mature processed HmuY (mpHmuY) lacking 25 N-terminal amino acids, which were not found in a native protein purified from P. gingivalis cells (Mihara and Holt 1993a;Lewis et al 2006). Since both HmuY variants showed identical properties, except for the slower migration of mpHmuY during electrophoresis under native conditions resulting from the different amino-acid composition, in this study we showed results for mpHmuY only.…”
Section: Biochemical Analysis Of Hmuy Proteinmentioning
confidence: 99%
“…These improvements made it possible to isolate substantial amounts (>30 mg per liter of the culture) of highly purified protein and facilitated a more detailed protein analysis. In this study, we characterized two HmuY variants: a mature HmuY protein (mHmuY) lacking 21 N-terminal amino acids and a mature processed HmuY (mpHmuY) lacking 25 N-terminal amino acids, which were not found in a native protein purified from P. gingivalis cells (Mihara and Holt 1993a;Lewis et al 2006). Since both HmuY variants showed identical properties, except for the slower migration of mpHmuY during electrophoresis under native conditions resulting from the different amino-acid composition, in this study we showed results for mpHmuY only.…”
Section: Biochemical Analysis Of Hmuy Proteinmentioning
confidence: 99%
“…Progress in molecular biological techniques has resulted in our increased interest in proteins which are directly encoded by DNA. Recently, a number of novel proteins specific to P. gingivalis have been identified and thoroughly investigated, i.e., proteases (2,7,11,31), a fibroblast-activating factor (19), heat shock protein (18), etc. However, the roles of these proteins in vivo remain speculative, and their usefulness as diagnostic tools has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mihara and Holt (27) isolated a 24-kDa protein from the outer membrane vesicles of P. gingivalis and found that the protein stimulated the proliferation of human gingival fibroblasts. These findings suggest that fibroblasts as well as lymphoid cells proliferate and produce various inflammatory cytokines in response to the cell surface components of black-pigmented anaerobes in periodontal tissues.…”
Section: Discussionmentioning
confidence: 99%